Risk Factors for Heart Failure and Coronary Artery Disease Mortality Based on the National Vital Statistics During a 25-Year Follow-up in Japan ― NIPPON DATA90 - Hirata, Aya; Ueshima, Hirotsugu; Okamura, Tomonori; Nakamura, Yasuyuki; Takashima, Naoyuki; Fujiyoshi, Akira; Harada, Akiko; Hayakawa, Takehito; Kubo, Kota; Miura, Katsuyuki; for the NIPPON DATA90 Research Group; Kadota, Aya; et al. (Circulation Journal, 2024)
Background: Prevention of heart failure (HF) is a public health issue. Using the National Vital Statistics, we explored risk factors for HF and coronary artery disease (CAD) mortality.Methods and Results: Altogether, 7,556 Japanese individuals aged ≥30 years in 1990 were followed over 25 years; of these, 139 and 154 died from HF and CAD, respectively. In multivariable Cox proportional hazard analysis, common risk factors for CAD and HF mortality were hypertension (hazard ratio [HR] 1.48 [95% confidence interval CI 1.00–2.20] and 2.31 [95% CI 1.48–3.61], respectively), diabetes (HR 2.52 [95% CI 1.63–3.90] and 2.07 [95% CI 1.23–3.50], respectively), and current smoking (HR 2.05 [95% CI 1.27–3.31) and 1.86 [95% CI 1.10–3.15], respectively). Specific risk factors for CAD were male sex, chronic kidney disease, history of cardiovascular disease, and both abnormal T and Q waves, with HRs (95% CIs) of 1.75 (1.05–2.92), 1.78 (1.19–2.66), 2.50 (1.62–3.88), and 11.4 (3.64–36.0), respectively. Specific factors for HF were current drinking (HR 0.43; 95% CI 0.24–0.78) and non-high-density lipoprotein cholesterol (non-HDL-C; HR 0.81; 95% CI 0.67–0.98). There was an inverse association between non-HDL-C and HF in those aged ≥65 years (HR 0.71; 95% CI 0.56–0.90), but not in those aged <65 years.Conclusions: We identified common risk factors for HF and CAD deaths; a history of cardiovascular disease was a specific risk for CAD.